1997
DOI: 10.1021/jp970415f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Palladium Nanoparticles with Interstitial Carbon by Sonochemical Reduction of Tetrachloropalladate(II) in Aqueous Solution

Abstract: The metal particles of an interstitial solid solution of palladium carbide, PdC x (0 < x ≤ 0.15), were synthesized at room temperature in aqueous solution during the reduction of tetrachloropalladate(II) with sonochemically produced organic radicals. The number of carbon atoms in the Pd particles were controlled by changing the concentration and the type of organic additives. The following mechanism of PdC formation is proposed:  (i) an active Pd cluster is formed during the synthesis of Pd particles, (ii) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
2

Year Published

2001
2001
2008
2008

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 22 publications
3
38
0
2
Order By: Relevance
“…Interstitial carbon in Pd may significantly alter the bulk and surface structure of Pd and can lead to catalytic deactivation in reactions involving hydrocarbons [3][4][5][6][7][8][9][10][11]. It is well known that Pd-Au catalysts exhibit much higher reactivity than pure Pd catalysts for certain reactions, e.g., in vinyl acetate synthesis the reactivity is improved by a factor of 5-7 by mixing Au with Pd [12].…”
Section: Introductionmentioning
confidence: 99%
“…Interstitial carbon in Pd may significantly alter the bulk and surface structure of Pd and can lead to catalytic deactivation in reactions involving hydrocarbons [3][4][5][6][7][8][9][10][11]. It is well known that Pd-Au catalysts exhibit much higher reactivity than pure Pd catalysts for certain reactions, e.g., in vinyl acetate synthesis the reactivity is improved by a factor of 5-7 by mixing Au with Pd [12].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Okitsu et al [21] reported the sonochemical synthesis of Pd nanoparticles on several alcohols, among them the 2-propanol. They found carbonaceous fragments in these Pd nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…Sonochemical reduction of metal ions is also a clean and easy preparation technique of metal nanoparticles [46][47][48]. In sonochemistry, three kinds of reaction should be considered: (a) the interior of the collapsing cavitation bubbles, (b) the interfacial region between bubbles and the bulk solution, and (c) bulk solution.…”
Section: Sonochemical Reduction Of Metal Ionsmentioning
confidence: 99%